Palliative care in pulmonary hypertension associated with congenital heart disease: systematic review and expert opinion - Andrew Constantine; Robin Condliffe; Paul Clift; Robert Tulloh; Konstantinos Dimopoulos; the CHAMPION Steering Committee (ESC Heart Failure, 2021)
Abstract Aims Pulmonary arterial hypertension (PAH) is common amongst patients with congenital heart disease (CHD). It is a severe and complex condition that adversely affects quality of life and prognosis. While quality of life questionnaires are routinely used in clinical pulmonary hypertension practice, little is known on how to interpret their results and manage PAH‐CHD patients with evidence of impaired health‐related quality of life, especially those with advanced disease and palliative care needs. Methods and results We performed a systematic review of studies concerning palliative care for people with PAH‐CHD, also reviewing the health‐related quality of life literature pertaining to these patients. Of 330 papers identified through initial screening, 17 were selected for inclusion. Underutilization of advance care planning and palliative care resources was common. Where palliative care input was sought, this was frequently late in the course of the disease. No studies provided evidence‐based clinical criteria for triggering referral to palliative care, a framework for providing tailored care in this patient group, or how to manage the risk of sudden cardiac death and implantable cardioverter defibrillators in advanced PAH‐CHD. We synthesize this information into eight important areas, including the impact of PAH‐CHD on quality of life, barriers to and benefits of palliative care involvement, advance care planning discussions, and end‐of‐life care issues in this complex patient group, and provide expert consensus on best practice in this field. Conclusions This paper presents the results of a systematic review and expert statements on the preferred palliative care strategy for patients with PAH‐CHD.